Coupling Liquid-Liquid Semimicroextraction with Micellar Electrokinetic Chromatography Through On-Capillary Decomposition for the Determination of 4-tert-Butylphenol and Bisphenol-A with Concentration Enhancement - Tang, Jing; Zheng, Sheng-Biao; Zhu, Jin-Kun; Wang, Tian-Lin (Asian Journal of Chemistry, 2011)
The method of methyl chloroacetate as an extraction solvent for coupling liquid-liquid semimicroextraction with micellar electrokinetic chromatography through on-capillary decomposition was applied to the determination of 4-tert-butylphenol and bisphenol-A with concen-tration enhancement. Equilibration time of extraction for 4-tert-butylphenol and bisphenol-A tested was reached in a relatively short period of time of 4.5 min. The concentration factors of 4-tertbutylphenol and bisphenol-A were 72 and 97, respectively. Linearity and detection limit of the method were also evaluated. Recoveries of 4-tert-butylphenol and bisphenol-A in drink water were examined. The recovery was obtained in the range of 97.0-106.5 %. The established method will be applied to the determination of bisphenol-A and alkylphenols in environmental waters.